PERANCANGAN MODEL WUJUD VISUAL TOKOH PEWAYANGAN DALAM PEMBENTUKAN IDENTITAS DAN WATAK TOKOH SEBAGAI ACUAN DESAIN KARAKTER DALAM KARYA DKV - Toto Haryadi Haryadi; Khamadi - (Institut Seni Indonesia Yogyakarta, 2014)
Shadow puppets is an arts which is still preserved until now. Recently, shadow puppets can becollaborated with tehcnology through act of revitalization. This is shown by many artworks in the field ofVisual Communication Design which adapt shadow puppets. The figures of shadow puppets become mainpart which is referred for designing of digital artwork, especially “character design”. On the other side,revitalization of puppets in form of character design is more concerned with aesthetic aspect than typicalidentity ones. Whereas, each figure has its own identity and temper which different from each other.This encourages the researchers to look for relation between visual form with typical identity of puppetfigures. The analysis of puppet visual form is required by taking sample based on the classification of thepuppet figures, namely: ‘denawa’, ‘punggawa’, ‘gagahan’, ‘satria’, ‘putran’, ‘putren’, ‘bayen’, ‘dagelan’, and‘kewanan’. The analysis is based on parameters such as: face expression, position and size of body, clothes,and attributes.